2022
DOI: 10.1097/yco.0000000000000794
|View full text |Cite
|
Sign up to set email alerts
|

Virtual recruitment and participant engagement for substance use research during a pandemic

Abstract: Purpose of reviewThe coronavirus disease 2019 pandemic resulted in cataclysmic changes to the research enterprise, causing a forced shutdown or rapid pivot to virtual methods. Adapting studies to the virtual environment also impacted recruitment and retention strategies. This review elucidated challenges and offered pragmatic recommendations, drawing on published literature and our prior work, to assist researchers in re-evaluating and amending best-practice techniques to bolster inclusive recruitment and stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Elliott et al 20 reported that social media knowledge translation strategies had an extended reach and higher level of engagement when co‐designed by patient or parent stakeholders compared with advertisements created solely by researchers. Engaging or consulting with community members from under‐represented populations or families on the feasibility and acceptability of the virtual recruitment approach may be useful to support the development of tailored content 45 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Elliott et al 20 reported that social media knowledge translation strategies had an extended reach and higher level of engagement when co‐designed by patient or parent stakeholders compared with advertisements created solely by researchers. Engaging or consulting with community members from under‐represented populations or families on the feasibility and acceptability of the virtual recruitment approach may be useful to support the development of tailored content 45 …”
Section: Resultsmentioning
confidence: 99%
“…Engaging or consulting with community members from under‐represented populations or families on the feasibility and acceptability of the virtual recruitment approach may be useful to support the development of tailored content. 45 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, the majority of research on substance use disorders that utilize virtual focus groups enrolls providers or professionals who work with individuals with substance use disorders ( 10 12 ). It is unclear whether recruitment and retention for this research method is or is not particularly challenging with persons who are actively using substances, as access to the Internet is not always stable and their comfort with video conferencing and remote survey completion can be variable ( 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…36 This elevated social isolation often resulted in healthcare disengagement, forgoing regular clinic visits. 38 Furthermore, patients may have also chosen not to use virtual or telehealth options for healthcare appointments because of discomfort with technology and accessibility, which disproportionately impacts those of older age as well as racial and ethnic minority subgroups. 39 Despite known recruitment challenges during the COVID-19 pandemic, especially for older adults, few articles included experiences with older adult participants.…”
mentioning
confidence: 99%